A method for preparing micro-nano sized CO2 capture material

Through the CAO/spinel CO2 capture material prepared by the dry ball grinding and solid -phase muddy synthetic synthetic legal system, the problem of low adsorption capacity of the existing CAO base materials during high temperature regeneration has been solved, and the efficient and low -cost CO2 arrest has been achieved. Collection and cycle stability.

CN118454634BActive Publication Date: 2025-01-28CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410595432.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-14
Publication Date
2025-01-28
Estimated Expiration
2044-05-14

AI Technical Summary

Technical Problem

The existing CaO-based CO2 capture materials have the problem that their adsorption capacity is lower than the theoretical value during high temperature regeneration, and the cost is high, making it difficult to achieve low-cost CO2 capture.

Method used

The CAO/spinel CO2 capture material with a dry -phase muddy synthesis method is used to prepare the micro -nano -size CAO/spinel CO2, and to improve the stability of the Mgal2O4 structure substrate and CO2 capture performance by doping the three -price metal ions.

Benefits of technology

It significantly improves the CAO -based absorbing agent's CO2 capture performance and cycle stability, reduces production costs, and improves the high temperature regeneration performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118454634B_ABST
    Figure CN118454634B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of preparation of environmental energy materials, and specifically relates to a method for preparing low-cost CaO / MgAl2O4 and CaO / trivalent ion-doped MgAl2O4 adsorbents. The present invention attempts for the first time to use dry ball milling + solid phase synthesis method and cheap raw materials to prepare high-quality CaO-based CO2 capture materials. In the present invention, trivalent ion-modified MgAl2O4 is used as a structural support material for CaO. After optimization of composition and process, the stability of the material in the repeated CO2 capture process of CaO is further improved; especially the high-temperature regeneration performance is improved. The preparation process of the present invention is simple and controllable, with low equipment requirements, and the obtained product has excellent performance and is easy to industrialize and apply.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of environmental energy materials, and specifically relates to a method for preparing a low-cost CaO trivalent ion-modified, micro-nano-sized MgAl2O4-based CO2 capture material. Background Art

[0002] The temperature goals of the Paris Agreement require global CO2 emissions to be halved by 2030 and reach net zero emissions by 2050. CO2 capture and utilization (CCU) technology is considered a promising way to achieve this goal. The cost of CO2 capture accounts for 70% of the cost of the entire engineering process, so it is very important to develop low-cost CO2 capture materials.

[0003] CO2 capture materials are mainly divided into low-temperature, medium-temperature and high-temperature capture materials according to their working temperature. CaO is a commonly used high-temperature capture material. It has a high working temperature range and can capture CO2 between 600℃ and 900℃. CaO forms calcium carbonate by chemical reaction with CO2, and then regenerates by heating after the reaction to release the captured CO2. CaO-based adsorbents have high adsorption capacity and low energy consumption, so they are widely used in high-temperature CO2 capture and utilization technology. The use of CaO for CO2 capture can effectively reduce the concentration of greenhouse gases in the atmosphere and provide important resources for the utilization of CO2. It can be applied to industrial waste gas treatment, CO2 capture in coal-fired power plants, and synthetic fuel production, and has important environmental and economic significance. The adsorption process of CaO can be divided into two steps: chemical control and diffusion control. First, CO2 reacts chemically with the surface of CaO, and then gradually diffuses into the interior of CaO along the pores. As the reaction proceeds, the newly generated calcium carbonate on the surface of the sample increases, eventually blocking the pores on the surface of CaO and preventing further diffusion of CO2. Therefore, the CO2 adsorption capacity of CaO-based adsorbents is often lower than its theoretical adsorption capacity. At present, the research strategies for CaO-based adsorbents include the preparation of CaO adsorbents. Oxides such as SiO2, Al2O3, and Y2O3 are used to stabilize CaO. The commonality of these structural matrices is that the Tammann temperature is high and the structure is stable. Therefore, the development and application of structural matrices with ultra-stable structures have been widely studied by researchers.

[0004] MgAl2O4 has excellent high-temperature stability and can be introduced into CaO-based CO2 capture materials to improve the CO2 capture performance of CaO-based adsorbents. In previous studies, our research group explored some methods for the solid-phase synthesis of CaO spinel CO2 capture materials. For example, in patent 2023112362426, the first CO2 capture capacity was 0.66g CO2 / g adsorbent. After 10 cycles, the capture capacity was 0.47g CO2 / g adsorbent, and the cycle retention rate was 71.2%. High-quality products. However, with the deepening of research and development, it was found that the MgAl2O4 structural matrix can be further optimized by trivalent ion doping, and the modified MgAl2O4 can be used as a structurally stable matrix to further improve the CO2 capture performance of the adsorbent. At present, the preparation method of ion-doped spinel is mainly a wet method, in which nitrates (aluminum nitrate, magnesium nitrate and nitrates of the required doping ions) are used in urea solution to obtain a precursor by coprecipitation, and then high-temperature sintering is prepared. The product obtained by this scheme has a large particle size and uneven distribution (Tabaza, WAI, Swart, HC, & Kroon, RE (2014). Luminescence of Ce doped MgAl2O4 prepared by the combustion method. Physica B: Condensed Matter, 439, 109-114.). Summary of the invention

[0005] Based on the findings of research and development, the present invention uses cheap raw materials for the first time and adopts dry ball milling + solid phase doping synthesis method to prepare CaO / spinel CO2 capture adsorbent with fine particle size and uniform distribution, excellent carbon dioxide capture performance and cyclic capture performance.

[0006] The present invention provides a method for preparing a micro-nano sized CO2 capture material, comprising the following steps:

[0007] S1: Dry-milling aluminum oxide, magnesium oxide, and oxide of an element to be doped to obtain a mixture; the oxide of the element to be doped is selected from at least one of lanthanum oxide, gallium oxide, and yttrium oxide, wherein the molar ratio of the element to be doped to aluminum is 0.01-0.03:0.97-0.99, preferably 0.02:0.98;

[0008] In S1, the speed of dry ball milling is greater than or equal to 750 r / min, and the ball milling time is greater than or equal to 8 h;

[0009] S2: sintering the mixture obtained in step S1 under air to dope MgAl2O4; the sintering temperature is 1190-1210°C; in the mixture, the molar ratio of trivalent metal ions to divalent metal ions is 2:1;

[0010] S3: According to the designed components, the doped spinel obtained in step S2 is ball-milled and mixed with the CaO precursor, and then sintered at high temperature to obtain a product, in which the mass ratio of CaO to doped spinel is 7-9:3-1; and the temperature of the high-temperature sintering is 890-910°C.

[0011] Preferably, in step S1, the rotation speed of the dry ball mill is 800 r / min, and the ball milling time is 10 h.

[0012] Preferably, in step S1, the oxide of magnesium is magnesium oxide; the oxide of lanthanum is lanthanum trioxide, the oxide of gallium is gallium trioxide, and the oxide of yttrium is yttrium trioxide.

[0013] Preferably, in step S2, the doped MgAl2O4 is selected from one of lanthanum-doped MgAl2O4, gallium-doped MgAl2O4 and yttrium-doped MgAl2O4.

[0014] Preferably, in step S2, the mixture is sintered in air or an inert atmosphere; the sintering temperature is 1200° C., and the holding time at the sintering temperature is 100 to 140 minutes.

[0015] Preferably, the sintering temperature in step S2 is 1200°C, and the sintering procedure is to heat up to A°C at 9-12°C / min, and then heat up to the sintering temperature at 4-6°C / min, and keep the temperature for 1-2h after reaching the sintering temperature; wherein the value of A is 480-520°C. The reason why the present invention adopts a heating system with two different heating rates is that the heating rate in the higher temperature stage affects the reaction between the oxide materials and the crystal growth.

[0016] The average particle size of aluminum oxide is 1 μm or less. The particle size of magnesium oxide is 1 μm or less, the particle size of lanthanum oxide is 1 μm or less, the particle size of gallium oxide is 1 μm or less, and the particle size of yttrium oxide is 1 μm or less.

[0017] Preferably, the CaO precursor includes calcium acetate, calcium carbonate, calcium nitrate and the like.

[0018] Preferably, in step S3, during ball milling and mixing, the rotation speed is 800 r / min and the ball milling time is 6 h.

[0019] During ball milling, the ball-to-material mass ratio is 16:1.

[0020] Preferably, the grinding balls used are composed of grinding balls with a diameter of 8 mm, grinding balls with a diameter of 10 mm, and grinding balls with a diameter of 15 mm, in a mass ratio of 8 mm grinding balls: 10 mm grinding balls: 15 mm grinding balls = 5:2.5:1.

[0021] Preferably, the mass ratio of CaO to spinel in the product is 8.0:2.0 or 9.0:1.0. Further preferably, the mass ratio of CaO to spinel in the product is 9.0:1.0.

[0022] The following steps are used to test the high temperature regeneration performance of the CaO / spinel-based adsorbent prepared in the present invention:

[0023] Step 1: After sampling, place it in a platinum crucible;

[0024] Step 2: Design the test program to heat the room temperature to 900°C, keep it warm for 5 minutes, and use argon as the gas;

[0025] Step 3: After the insulation is completed, the temperature is reduced from 900°C to 700°C and maintained at 700°C for 30 minutes, and the gas introduced is CO2;

[0026] Step 4: Raise the temperature from 700°C to 900°C and keep at 900°C for 10 minutes, with nitrogen as the gas.

[0027] Step 5: Repeat steps 3 to 5.

[0028] Beneficial Effects of the Invention

[0029] 1. The present invention provides a CaO / spinel adsorbent, which includes CaO and MgAl2O4, lanthanum-doped MgAl2O4, gallium-doped MgAl2O4, and yttrium-doped MgAl2O4. Various types of spinels are used as structural support materials for CaO. After optimization of composition and process, the stability of CaO materials in repeated CO2 capture processes is further improved; especially the high-temperature regeneration performance is improved.

[0030] 2. The preparation method of the CaO / spinel adsorbent provided by the present invention has low equipment requirements, a wide source of raw materials with low prices, simple steps, high controllability, and is easy for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The XRD patterns of MgAl2O4, lanthanum-doped MgAl2O4, gallium-doped MgAl2O4, and yttrium-doped MgAl2O4 prepared in Example 1, Example 2, Example 3, and Example 4;

[0032] Figure 2 is the XRD pattern of the CaO / MgAl2O4 adsorbent prepared in Example 5;

[0033] Figure 3 is the XRD pattern of the CaO / lanthanum-doped MgAl2O4 adsorbent prepared in Example 5;

[0034] Figure 4 is the XRD pattern of the CaO / gallium-doped MgAl2O4 adsorbent prepared in Example 5;

[0035] Figure 5 is the XRD pattern of the CaO / yttrium-doped MgAl2O4 adsorbent prepared in Example 5;

[0036] Figure 6 is a graph of CO2 capture performance of the CaO / MgAl2O4 adsorbent prepared in Example 5;

[0037] Figure 7 is a graph of CO2 capture performance of the CaO / lanthanum-doped MgAl2O4 adsorbent prepared in Example 5;

[0038] Figure 8 is a graph showing the CO2 capture performance of the CaO / gallium-doped MgAl2O4 adsorbent prepared in Example 5;

[0039] Fig. 9 is a graph showing the CO2 capture performance of the CaO / yttrium-doped MgAl2O4 adsorbent prepared in Example 5;

[0040] Fig.10 is the SEM and element distribution diagram of lanthanum-doped MgAl2O4 prepared in Example 2;

[0041] Fig.11 is the SEM and element distribution diagram of gallium-doped MgAl2O4 prepared in Example 3;

[0042] Fig.12 is the SEM and element distribution diagram of yttrium-doped MgAl2O4 prepared in Example 4;

[0043] Fig.13 This is a graph showing the CO2 capture performance of the CaO / lanthanum-doped MgAl2O4 adsorbent prepared by wet ball milling in Example 1.

[0044] Fig.14 is the SEM and element distribution diagram of the CaO / lanthanum-doped MgAl2O4 adsorbent prepared in Example 5;

[0045] Fig.15 is the SEM and element distribution diagram of the CaO / yttrium-doped MgAl2O4 adsorbent prepared in Example 5;

[0046] Fig.16 This is the SEM and element distribution diagram of the CaO / MgAl2O4 adsorbent prepared in Example 5. DETAILED DESCRIPTION

[0047] On the one hand, an embodiment of the present invention provides a CaO / spinel adsorbent, which includes CaO and MgAl2O4, lanthanum-doped MgAl2O4, gallium-doped MgAl2O4, and yttrium-doped MgAl2O4. Various types of spinels are used as structural support materials of CaO to further improve the stability of the CaO adsorbent during repeated CO2 capture. On the other hand, an embodiment of the present invention also provides a preparation method of the above-mentioned CaO / spinel adsorbent.

[0048] In order to better understand the above technical solution, the above technical solution will be described in detail below in combination with specific implementation methods.

[0049] Example 1

[0050] This example provides a method for preparing MgAl2O4, specifically:

[0051] S1: Commercial aluminum oxide (particle size less than 1 micron) and magnesium oxide (particle size less than 1 micron) were dry-milled for 10 hours at a ball-to-material mass ratio of 16:1 at a speed of 800 r / min. Subsequently, MgAl2O4 was prepared by high-temperature sintering. The XRD pattern of the prepared material is shown in Figure 1. Figure 1 shown.

[0052] In S1, aluminum oxide and magnesium oxide are weighed at an Al:Mg atomic ratio of 2:1.

[0053] The sintering temperature in S1 is 1200°C, the sintering procedure is 0-500°C, 10°C / min, 500-1200°C, 5°C / min, and heat preservation for 2 hours. The average particle size of the obtained product is about 5 microns.

[0054] Example 2

[0055] This example provides a method for preparing lanthanum-doped MgAl2O4, specifically:

[0056] S1: Weigh individual oxides of aluminum oxide (particle size less than 1 micron), lanthanum oxide (particle size less than 1 micron) and magnesium oxide (particle size less than 1 micron) according to the ratio of the sum of trivalent lanthanum and trivalent aluminum being 2 (wherein the molar ratio of trivalent lanthanum ions and trivalent aluminum ions is 0.02:0.98) and divalent magnesium ions being 1. Place the mixture in an agate ball mill at 800 r / min and dry-mill for 10 hours (the ball-to-material mass ratio is 16:1; the grinding balls used are composed of 8mm diameter grinding balls, 10mm diameter grinding balls, and 15mm diameter grinding balls in a mass ratio of 8mm diameter grinding balls: 10mm diameter grinding balls: 15mm diameter grinding balls = 5:2.5:1). Subsequently, lanthanum-doped MgAl2O4 is prepared by high-temperature sintering. The XRD patterns, SEM patterns and element distribution patterns of the prepared materials are shown as follows, respectively. Figure 1 , Fig.10 As shown in Figure 2, the average particle size of MgAl2O4 doped with La is smaller than that of MgAl2O4.

[0057] In S1, the trivalent ion and divalent ion atoms are weighed at a ratio of 2:1.

[0058] In S1, the sintering temperature is 1200°C, the sintering procedure is 0-500°C, 10°C / min, 500-1200°C, 5°C / min, and the temperature is kept for 2 hours. The average particle size of the obtained product is less than 5 microns.

[0059] Example 3

[0060] This example provides a method for preparing gallium-doped MgAl2O4, specifically:

[0061] S1: Weigh individual oxides of aluminum oxide (particle size less than 1 micron), gallium oxide (particle size less than 1 micron) and magnesium oxide (particle size less than 1 micron) according to the ratio of the sum of trivalent gallium and trivalent aluminum to 2 (wherein the molar ratio of trivalent gallium ions and trivalent aluminum ions is 0.02:0.98) and divalent magnesium ions to 1. Place the mixture in an agate ball mill at 800r / min and dry-mill for 10 hours (the ball-to-material mass ratio is 16:1; the grinding balls used are composed of 8mm diameter grinding balls, 10mm diameter grinding balls, and 15mm diameter grinding balls in a mass ratio of 8mm diameter grinding balls: 10mm diameter grinding balls: 15mm diameter grinding balls = 5:2.5:1). Subsequently, gallium-doped MgAl2O4 is prepared by high-temperature sintering. The XRD patterns, SEM patterns and element distribution patterns of the prepared materials are shown below. Figure 1 , Fig.11 The average particle size of the obtained product is less than 5 microns.

[0062] In S1, the trivalent ion and divalent ion atoms are weighed at a ratio of 2:1.

[0063] In S1, the sintering temperature is 1200°C, the sintering procedure is 0-500°C, 10°C / min, 500-1200°C, 5°C / min, and the temperature is kept for 2 hours. The average particle size of the obtained product is less than 5 microns.

[0064] Example 4

[0065] This example provides a method for preparing yttrium-doped MgAl2O4, specifically:

[0066] S1: Weigh individual oxides of aluminum oxide (particle size less than 1 micron), yttrium oxide (particle size less than 1 micron) and magnesium oxide (particle size less than 1 micron) according to the ratio of the sum of trivalent yttrium and trivalent aluminum to 2 (the molar ratio of trivalent yttrium and trivalent aluminum is 0.02:0.98) and divalent magnesium to 1. Place the mixture in an agate ball mill at 800r / min and dry-mill for 10 hours (the ball-to-material mass ratio is 16:1; the grinding balls used are composed of 8mm diameter grinding balls, 10mm diameter grinding balls, and 15mm diameter grinding balls in a mass ratio of 8mm diameter grinding balls: 10mm diameter grinding balls: 15mm diameter grinding balls = 5:2.5:1). Subsequently, yttrium-doped MgAl2O4 is prepared by high-temperature sintering. The XRD patterns, SEM patterns and element distribution patterns of the prepared materials are shown below. Figure 1 , Fig.12 As shown in Figure 2, the particle size distribution of yttrium-doped MgAl2O4 is smaller than that of MgAl2O4.

[0067] In S1, the trivalent ion and divalent ion atoms are weighed at a ratio of 2:1.

[0068] The sintering temperature in S1 is 1200°C, and the sintering procedure is 0-500°C, 10°C / min, 500-1200°C, 5°C / min, and insulation for 2h. The average particle size of the product is less than 5 microns. The XRD diagrams of various types of spinels prepared in Examples 1-4. The peaks of the spinel structure are shifted to the left. This is mainly because the radius of the aluminum ion is 53pm, the radius of the gallium ion is 62pm, the radius of the yttrium ion is 90pm, and the radius of the lanthanum ion is 103pm. As the radius of the doped ions increases, the lattice is distorted, which increases the interplanar spacing. According to the Bragg equation, it can be concluded that the diffraction angle shifts to a small angle.

[0069] Example 5

[0070] This example provides a method for preparing CaO / MgAl2O4 and CaO / trivalent ion-doped MgAl2O4 adsorbents, the steps comprising:

[0071] S1: MgAl2O4 and various doped spinels prepared in Examples 1-4 were ball-milled and mixed with calcium acetate (the ball-to-material mass ratio was 16:1; the grinding balls used were 8 mm diameter grinding balls, 10 mm diameter grinding balls, and 15 mm diameter grinding balls in a mass ratio of 8 mm diameter grinding balls: 10 mm diameter grinding balls: 15 mm diameter grinding balls = 5:2.5:1), dry-milled for 6 hours, and sintered at high temperature to obtain CaO / MgAl2O4, CaO / lanthanum-doped MgAl2O4, CaO / yttrium-doped MgAl2O4, and CaO / gallium-doped MgAl2O4 adsorbents. The XRD patterns of the prepared adsorbents are as follows: Figure 2-6 As shown. SEM images and element distribution diagrams, such as Figure 14-16 shown.

[0072] In step S1, various types of spinels are used as structural support materials for CaO.

[0073] The mass ratio of CaO to doped MgAl2O4 in the prepared product is 9.0:1.0.

[0074] In step S1, the high temperature sintering temperature of CaO / MgAl2O4, CaO / lanthanum-doped MgAl2O4, CaO / yttrium-doped MgAl2O4, and CaO / gallium-doped MgAl2O4 adsorbents is 900° C. It can be seen that the particle sizes of CaO / lanthanum-doped MgAl2O4 and CaO / yttrium-doped MgAl2O4 adsorbents are significantly smaller than that of CaO / MgAl2O4 adsorbent, further proving that ion-doped spinel plays an important role in refining the adsorbent particle size.

[0075] Example 6

[0076] According to the method of Example 5, this example will test the CO2 capture performance of the prepared pure CaO and various spinel-based adsorbents of CaO. The main steps include:

[0077] S1: Take about 10 mg of each of the CaO / MgAl2O4, CaO / lanthanum-doped MgAl2O4, CaO / yttrium-doped MgAl2O4, and CaO / gallium-doped MgAl2O4 adsorbents prepared in Example 5 and place them in a platinum crucible.

[0078] S2: The test procedure is designed to raise the temperature from room temperature to 900°C, keep it at that temperature for 5 minutes, and use argon as the gas.

[0079] S3: After the insulation is completed, the temperature is reduced from 900°C to 700°C and maintained at 700°C for 30 minutes, and CO2 is introduced as gas (carbonization).

[0080] S4: Raise the temperature from 700°C to 900°C and keep at 900°C for 10 minutes, with nitrogen as the gas (regeneration).

[0081] S5: Reduce the temperature from 900°C to 700°C, and repeat steps S3-S5 10 times.

[0082] Testing the CO2 capture performance of CaO / MgAl2O4 adsorbent:

[0083] Each time, 9.33 mg of the CaO / MgAl2O4 adsorbent prepared in Example 5 was weighed (repeated 5 times) and placed in a platinum crucible compatible with a thermogravimetric analyzer to test the CO2 capture performance of the adsorbent. The main steps include:

[0084] The CO2 capture performance and cycle performance of the CaO / MgAl2O4 adsorbent prepared in Example 5 are as follows: Figure 7 As shown, from Figure 7 It can be seen that the average CO2 capture capacity of the CaO / MgAl2O4 adsorbent for the first time is 0.65g CO2 / g adsorbent. After 10 cycles, the average CO2 capture capacity is 0.45g CO2 / g adsorbent, and the average cycle retention rate is 69.2%.

[0085] Testing the CO2 capture performance of CaO / La-doped MgAl2O4 adsorbent:

[0086] 9.67 mg of the CaO / lanthanum-doped MgAl2O4 adsorbent prepared in Example 5 was weighed each time (repeated 5 times) and placed in a platinum crucible compatible with a thermogravimetric analyzer to test the CO2 capture performance of the CaO / spinel-based adsorbent.

[0087] The CO2 capture performance and cycle performance of the CaO / lanthanum-doped MgAl2O4 adsorbent prepared in Example 5 are as follows: Figure 7 As shown, from Figure 7 It can be seen that the average CO2 capture capacity of the CaO / MgAl2O4 adsorbent for the first time is 0.66g CO2 / g adsorbent, and after 10 cycles, the average capture capacity is 0.50g CO2 / g adsorbent. The cycle retention rate is 75.8%, and the adsorption capacity is improved compared with the CaO / MgAl2O4 adsorbent.

[0088] Testing the CO2 capture performance of CaO / gallium-doped MgAl2O4 adsorbent:

[0089] 9.27 mg of the CaO / gallium-doped MgAl2O4 adsorbent prepared in Example 5 was weighed each time (repeated 5 times) and placed in a platinum crucible compatible with a thermogravimetric analyzer to test the CO2 capture performance of the CaO / spinel-based adsorbent.

[0090] The CO2 capture performance and cycle performance of the CaO / gallium-doped MgAl2O4 adsorbent prepared in Example 5 are as follows: Figure 8 As shown, from Figure 8 It can be seen that the average CO2 capture capacity of the first CO2 capture of CaO / gallium-doped MgAl2O4 adsorbent is 0.68g CO2 / g adsorbent. After 10 cycles, the average capture capacity is 0.47g CO2 / g adsorbent.

[0091] Testing the CO2 capture performance of CaO / yttrium-doped MgAl2O4 adsorbent:

[0092] 9.41 mg of the CaO / yttrium-doped MgAl2O4 adsorbent prepared in Example 5 was weighed each time and placed in a platinum crucible compatible with a thermogravimetric analyzer to test the CO2 capture performance of the CaO / spinel-based adsorbent.

[0093] The CO2 capture performance and cycle performance of the CaO / yttrium-doped MgAl2O4 adsorbent prepared in Example 5 are as follows: Fig. 9 As shown, from Fig. 9 As can be seen from the graph, the average CO2 capture capacity of the CaO / lanthanum-doped MgAl2O4 adsorbent is 0.66 g CO2 / g adsorbent for the first cycle, and after 10 cycles, the average capture capacity is 0.48 g CO2 / g adsorbent. The cycle retention rate is 72.7%.

[0094] Example 7

[0095] Other conditions are consistent with those in Example 2, except that the molar ratio of trivalent lanthanum ions to trivalent aluminum ions is 0.01:0.99. Then, the same process and parameters as in Example 5 are used to prepare a CaO / lanthanum-doped MgAl2O4 adsorbent (whose particle size distribution is about 5 microns). Then, the same detection process as in Example 6 is used to detect its performance. The first CO2 capture capacity of the obtained product is 0.65g CO2 / g adsorbent, and after 10 cycles, the capture capacity is 0.49g CO2 / g adsorbent. The cycle retention rate is 75.4%.

[0096] Example 8

[0097] Other conditions were the same as those in Example 2, except that the molar ratio of trivalent lanthanum ions to trivalent aluminum ions was 0.03:0.97. Then, the same process and parameters as in Example 5 were used to prepare the CaO / lanthanum-doped MgAl2O4 adsorbent (whose particle size distribution was about 5 microns). Then, the same detection process as in Example 6 was used to detect its performance. The average CO2 capture capacity of the obtained product was 0.68 g CO2 / g adsorbent for the first time, and after 10 cycles, the average capture capacity was 0.47 g CO2 / g adsorbent. The cycle retention rate was 69.1%.

[0098] Example 9

[0099] Other conditions are consistent with Examples 2 and 5, except that the mass ratio of CaO to lanthanum-doped MgAl2O4 is 7.0:3.0.

[0100] Then, the same testing process as in Example 6 was used to test its performance. The average CO2 capture capacity of the obtained product was 0.63 g CO2 / g adsorbent for the first time, and after 10 cycles, the average capture capacity was 0.47 g CO2 / g adsorbent. The cycle retention rate was 74.6%.

[0101] Example 10

[0102] The other conditions are the same as those of Examples 2 and 5, except that the mass ratio of CaO to lanthanum-doped MgAl2O4 is 9.0:1.0.

[0103] Then, the same testing process as in Example 6 was used to test its performance. The initial CO2 capture capacity of the obtained product was 0.69 g CO2 / g adsorbent, and after 10 cycles, the capture capacity was 0.51 g CO2 / g adsorbent. The cycle retention rate was 73.9%.

[0104] Comparative Example 1

[0105] This comparative example provides a method for preparing a CaO / lanthanum-doped spinel adsorbent, the steps comprising:

[0106] S1: After ball milling and mixing the lanthanum-doped MgAl2O4 prepared in Example 4 with calcium acetate (the ball-to-material mass ratio is 16:1; the grinding balls used are composed of grinding balls with a diameter of 8 mm, grinding balls with a diameter of 10 mm, and grinding balls with a diameter of 15 mm, and the mass ratio of grinding balls with a diameter of 8 mm: grinding balls with a diameter of 10 mm: grinding balls with a diameter of 15 mm = 5:2.5:1), wet ball milling for 6 hours, the solvent is deionized water, and placed in a box oven to dry overnight at a temperature of 80°C. Then high-temperature sintering is performed to obtain CaO / lanthanum-doped MgAl2O4 adsorbent. .

[0107] In step S1, lanthanum-doped MgAl2O4 is used as a structural support material for CaO.

[0108] The mass ratio of CaO to lanthanum-doped MgAl2O4 in the prepared product is 9.0:1.0.

[0109] The high temperature sintering temperature of CaO / lanthanum doped MgAl2O4 (whose particle size distribution is about 5 microns) in step S1 is 900°C.

[0110] Testing the CO2 capture performance of CaO / La-doped MgAl2O4 adsorbent:

[0111] Each time, 9.37 mg of the CaO / yttrium-doped MgAl2O4 adsorbent prepared in Comparative Example 1 was weighed and placed in a platinum crucible compatible with the thermogravimetric analyzer to test the CO2 capture performance of the CaO / lanthanum-doped spinel adsorbent. The average CO2 capture capacity of the CaO / lanthanum-doped MgAl2O4 adsorbent prepared by wet ball milling was 0.68 g CO2 / g adsorbent for the first time. After 10 cycles, the average capture capacity was 0.45 g CO2 / g adsorbent. The cycle retention rate was 66.2% ( Fig.13 ).

[0112] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a micro-nano sized CO2 capture material, characterized in that: The steps include: S1: Dry-milling aluminum oxide, magnesium oxide, and oxide of an element to be doped to obtain a mixture; the oxide of the element to be doped is selected from one of lanthanum oxide and yttrium oxide, wherein the molar ratio of the element to be doped to aluminum is 0.01-0.03:0.97-0.99; the average particle size of aluminum oxide is less than or equal to 1 μm, the particle size of magnesium oxide is less than or equal to 1 μm, the particle size of lanthanum oxide is less than or equal to 1 μm, and the particle size of yttrium oxide is less than or equal to 1 μm; S2: sintering the mixture obtained in step S1 under air to obtain doped MgAl2O4; in the mixture, the molar ratio of trivalent metal ions to divalent metal ions is 2:1; S3: According to the designed components, the doped MgAl2O4 obtained in step S2 is ball-milled and mixed with the CaO precursor, and sintered at high temperature to obtain a product, wherein the mass ratio of CaO to doped spinel in the product is 7-9:3-1; the temperature of the high-temperature sintering is 890-910°C; In step S1, the rotation speed of the dry ball mill is 800 r / min, and the ball milling time is 10 h; In step S1, the magnesium oxide is magnesium oxide; the lanthanum oxide is lanthanum trioxide; and the yttrium oxide is yttrium trioxide; In step S2, the doped MgAl2O4 is selected from one of lanthanum-doped MgAl2O4 and yttrium-doped MgAl2O4; In step S2, the sintering temperature is 1200°C; the sintering procedure is: heating to A°C at 9-12°C / min, and then heating to the sintering temperature at 4-6°C / min. After reaching the sintering temperature, keep warm for 2 hours, wherein the value of A is 480-520°C; The CaO precursor includes calcium acetate, calcium carbonate and calcium nitrate; In step S3, during ball milling and mixing, the rotation speed is 800 r / min, and the ball milling time is 6 h; during dry ball milling, the ball-to-material mass ratio is 16:1; The grinding balls used are composed of grinding balls with a diameter of 8 mm, grinding balls with a diameter of 10 mm, and grinding balls with a diameter of 15 mm, and the mass ratio is 8 mm grinding balls: 10 mm grinding balls: 15 mm grinding balls = 5:2.5:

1.

2. The method for preparing a micro-nano sized CO2 capture material according to claim 1, characterized in that: The mass ratio of CaO to doped spinel in the product is 8.0:2.0 or 9.0:1.0.

Citation Information

Patent Citations

  • Preparation method of low-cost calcium oxide spinel carbon dioxide trapping material

    CN117181183A

  • KR20190121679A